2017
DOI: 10.3892/ol.2017.6792
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the key miRNAs associated with survival time in stomach adenocarcinoma

Abstract: Stomach adenocarcinoma (STAD) is one of the leading causes of cancer morbidity and mortality worldwide. The present study aimed to identify the microRNAs associated with STAD survival time. The clinical information and microarray miRNA and mRNA expression profiles of STAD patients were downloaded from The Cancer Genome Atlas. Differential expression (DE) analysis was performed to identify DEmiRNAs and DEmRNAs in STAD. The DEmiRNAs associated with the survival time of patients with STAD were identified through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Approximately 90% of the miRNA reads (∼8.5 million reads) were concentrated on the 35 most expressed miRNAs. The number and representativity of D. E. expressed miRNAs identified in this study is similar to other studies that performed miRNome analysis (Hou et al, 2011; Maltseva et al, 2014; Liu et al, 2015; Castro-Magdonel et al, 2017; Liang et al, 2017).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Approximately 90% of the miRNA reads (∼8.5 million reads) were concentrated on the 35 most expressed miRNAs. The number and representativity of D. E. expressed miRNAs identified in this study is similar to other studies that performed miRNome analysis (Hou et al, 2011; Maltseva et al, 2014; Liu et al, 2015; Castro-Magdonel et al, 2017; Liang et al, 2017).…”
Section: Resultssupporting
confidence: 87%
“…Studies that analyzed the data from miRNA sequencing in gastric cancer demonstrated their deregulation in this type of tumor (Assumpção et al, 2015; Darnet et al, 2015; Liu et al, 2015; Liang et al, 2017). Among the miRNAs found in these studies, hsa-miR-99a , -miR-100 , -miR-133a/b-3p , -miR-135b , -miR-141 , -miR-143 , -miR-145 , -miR-148a , -miR-196a/b , -miR-200a , -miR-218-1 , -miR-215 , and -miR-490 were also observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…STAD is the second leading cause of cancer-related death due to its poor prognosis [2,3]. The identification of a new valuable prognostic marker for STAD becomes more urgent [23].…”
Section: Discussionmentioning
confidence: 99%
“…Most patients with STAD are diagnosed at the advanced stage of the disease. The 5-year survival rate of these patients is very low, and the prognosis of STAD remains poor [2,3]. Therefore, it is urgent to identify a new valuable prognostic marker for STAD.…”
Section: Introductionmentioning
confidence: 99%